Ticagrelor versus clopidogrel in the management of acute myocardial infarction. Issue 4 (4th July 2019) - Volney, Candice; Collins, Anthony; Adams, Sarah
ABSTRACT: Hypothesis : In the care of acute myocardial infarction, ticagrelor attenuates post-ischemic myocardial damage and inhibits platelet activity to a greater extent than clopidogrel. Methods : Scholarly articles published in the last 10 years were compiled from a PubMed MeSH search focusing on acute coronary infarction and the antiplatelet therapies clopidogrel and ticagrelor. The databases used were PubMed, Google Scholar, Dynamed, and EBSCOhost. Eight articles were chosen based on subject matter related to the hypothesis, including cardioprotective effects, mortality benefits, platelet reactivity, angiographic effects, and electrocardiography changes. Results : Evidence from randomized clinical trials demonstrates that ticagrelor reduces infarct size, prevents remodeling, and reduces mortality rate after acute myocardial infarction to a greater extent than clopidogrel. However, some angiography studies show no difference between the two treatment regimes. Two articles show that ticagrelor is more effective in treating individuals with high platelet reactivity (HPR). In addition, there is some evidence of increased dyspnea and significant bleeding with ticagrelor. Discussion : Although there is growing evidence that ticagrelor is the better antiplatelet drug post-acute coronary infarction, more research needs to be done to determine the situations in which ticagrelor provides the optimal treatment regime in regards to cardioprotective effects, antiplatelet effects and an overall decrease in mortality. Conclusion : Ticagrelor was found to be superior to clopidogrel in relation to cardioprotective effects, mortality, and antiplatelet activity.